Difference Long Irradiation on The Growth Rate of Kappaphycus Alvarezii - Lulu Lutfiati; Nunik Cokrowati; Fariq Azhar (Jurnal Biologi Tropis, 2022)
The study aimed to find out the long-standing difference in irradiation to the growth rate of Kappaphycus alvarezii in controlled containers. The method used is experimental. This study used a Complete Randomized Design (RAL) using four (4) treatments with 3 repeats, namely the treatment of P1 control (without irradiation), P2 (8 hours of irradiation), P3 (10-hour irradiation), P4 (12-hour irradiation). The data were analyzed using analysis of variance (ANOVA) at a rate of 5% with a confidence interval of 95% and continued with the Duncan test. In this study, the average results of absolute weight and the highest specific daily growth rate at P4 treatment of 25.67ÃÂ±1.53 gr, 3.30ÃÂ±0.06%, followed by P3 treatment 21ÃÂ±2 gr, 3.11ÃÂ±0.09%, P2 treatment 16ÃÂ±1 gr, 2.87ÃÂ±0.06%, and lowest P1 treatment 12.33ÃÂ±2.08 gr, 2.63ÃÂ±0.15%. The average value of light intensity in each treatment is P1 1053ÃÂ±41.00 lux, P2 1256ÃÂ±27.71 lux, P3 1479ÃÂ±0.58 lux, and P4 1668ÃÂ±34.64 lux. Water quality parameters during maintenance are in the normal limit range for seaweed maintenance. D treatment produces the highest growth value this is because the light is an energy source in the process of photosynthesis, in chlorophyll plants, photosynthesis is the main process determining the rate of growth. The quality and amount of light that enters affects the growth of seaweed. This research concluded that the maintenance of Kappaphycus alvarezii in controlled containers with different irradiation had a significant effect on growth. 12 hours irradiation (P4) gave the best growth with an absolute weight of 16.00 g, and a specific growth rate of 4.06% per day and gave the highest chlorophyll-a value of 2.72 mg/l. Meanwhile, the highest phycoerythrin value was found in (P1) without irradiation, which was 4.58 mg/l.